Policy coherence: Essential to strengthening policy impact across CGIAR initiatives - Nicol, Alan; Ramírez, Juan Carlos Sanchez; Maru, Joyce; Victor, Michael (CGIAR System Organization, 2023)
Complexity can be overwhelming and the CGIAR initiatives are a contributing factor. Numerous countries face intense policy challenges as they tackle interlinked food, water, and energy emergencies amid a climate crisis, and some host initiatives engaging in different and sometimes overlapping policy spaces. Supporting the poorest and most vulnerable communities requires policy that is well targeted, effectively implemented and joined up. The joining up is often touted, but difficult to achieve, especially beyond the level of paper coherence and in the more bruising world of actual policy implementation.